Thermal-induced nonlinearity of Ag Nano-Fluid prepared using y radiation method - Esmaeil Shahriari,; Mahmood .W Mat Yunus,; Zainal Abidin Talib,; Elias Saion, (Universiti Kebangsaan Malaysia, 2011)
The non-linear refractive index of Ag nano-fluids prepared by γ-radiation method was investigated using a single beam z-scan technique. Under CW 532 nm laser excitation with power output of 40 mW, the Ag nano-fluids showed a large thermal-induced non-linear refractive index. In the present work it was determined that the non-linear refractive index for Ag nano-fluids is -4.80×10-8 cm2/W. The value of Δn0 was calculated to be -2.05×10-4. Our measurements also confirmed that the non-linear phenomenon was caused by the self-defocusing process making them good candidates for non linear optical devices.